Use of ARFI elastography in the prediction of placental invasion anomaly via a new Virtual Touch Quantification Technique. (3rd October 2018) - Cim, Numan; Tolunay, Harun Egemen; Boza, Baris; Arslan, Harun; Ates, Can; İlik, İbrahim and Tezcan, Fatih Mehmet and Yıldızhan, Recep and Sahin, Hanım Guler and Yavuz, Alpaslan
Abstract: We aimed to evaluate the efficiency of placental elasticity in predicting a placental invasion anomaly with the Virtual Touch Quantification (VTQ) technique. Pregnant women in the third trimester with suspected placental invasion anomaly were enrolled into the research ( n = 58). The placenta was evaluated and divided into three equal parts as foetal edge (inner 1/3 of placenta), maternal edge (outer 1/3 of placenta) and the central part (central 1/3 of placenta). Shear wave velocity (SWV) measurements were used in the elastographic evaluation of placentas by VTQ. We performed the measurements at the different regions of placenta for sampling the variety areas of the placenta. Acoustic Radiation Force Impulse (ARFI) Elastography scores were significantly higher in the group in which an invasion was detected during the surgery of patients with preoperative placental invasion suspicion. A significant difference in the measurements of the inner, central and outer third of the placenta between the groups was found ( p < .001). In this study, we have shown higher SWV scores of placental measurements of the patients with preoperative suspected anomalies and an invasion detected during their surgery. These findings may reflect an event at the tissue elasticity level and we hope that the use of the VTQ technique may contribute to an early prediction of placental invasions before surgery in the future via new research. Impact statement: What is already known on this subject? Placenta invasion anomalies (PIA's) are characterized by haemorrhages which can threat the mother's life. Placental invasion anomalies are among the most important causes of maternal mortality and morbidity. Early diagnosis is very important condition in reducing the mortality and morbidity. Gray scale ultrasonography (US) is mostly used in early diagnosis of PIA's. Acoustic radiation force impulse elastography (ARFI) is a new elastographic ultrasonography technic. We aimed to evaluate a new method in the early diagnosis of PIA's using ARFI technique. There is no study in the diagnosis of PIA's by ARFI in the literature to our knowledge. We think that this original study will contribute to the literature. What do the results of this study add? We showed the accuracy of ARFI in determination of PIA's. ARFI scores were significantly higher in the group in which invasion was detected during surgery of patients with preoperative placental invasion suspicion. What are the implications are of these findings for clinical practice and/or further research? Our findings may reflect an event at the tissue elasticity level and we hope that the use of VTQ technique may contribute to early predict of placental invasions before surgery in the future via new researches. Early diagnosis of placental invasion anomalies may reduce mortality and morbidity.